OVERCOMING CULTURAL SHOCK AMONG INTERNATIONAL STUDENTS - Nakonechna, Lyubov (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2023)
The article addresses the issue of cultural shock among international students studying in higher education institutions in foreign countries. It examines the main factors contributing to cultural shock, analyzes the peculiarities of adaptation of international students to new cultural and linguistic environments, discusses effective adaptation strategies, intercultural communication, and the specifics of psychological preparation for international students in Ukrainian and German-speaking environments. Recommendations for overcoming cultural shock are provided. _________________ References: • Oberg, K. «Cultural Shock: Adjustment to new cultural environments.» Practical Anthropology 7 (1960): 177- 182. • Lysgaard, S. «Adjustment in foreign society: Norwegian Fulbright Visiting the United States.» International Social Sciences Bulletin7 (1) (1955). • Argil, M. Social encounters (London, 1976).